Progress in the study of antibody-drug conjugates for the treatment of cervical cancer - Zhai, Congcong; Cui, Yan; Guo, Ling; Chen, Cixiang; Song, Yanfang; Zhong, Jinghua; Wang, Yili (Frontiers in Oncology, 2024)
Cervical cancer is the second most prevalent malignancy affecting women's health globally, and the number of morbidity and mortality from cervical cancer continues to rise worldwide. The 5-year survival rate of patients with recurrent or metastatic cervical cancer is significantly reduced, and existing treatment modalities have low efficacy and high adverse effects, so there is a strong need for new, effective, and well-tolerated therapies. Antibody-drug conjugates (ADCs) are a new targeted therapeutic modality that can efficiently kill tumor cells. This review aims to summarize the composition, research, and development history and mechanism of action of ADCs, to review the research progress of ADCs in the treatment of cervical cancer, and to summarize and prospect the application of ADCs.